Biering-Sorensen test performance of Japanese young males: comparison with other ethnicities and relationship to electromyography, near-infrared spectroscopy and exertion ratings - Coleman, J.; Straker, Leon; Campbell, Amity; Izumi, H.; Smith, Anne (Taylor & Francis Ltd., 2011)
Back muscle endurance is a predictor of future low back pain and is commonly assessed using the Biering-Sorensen Test (BST). Differences exist between ethnic groups that may affect the performance and interpretation of the BST and should be investigated. This study’s aim was to explore objective and subjective measures of the BST in a Japanese group in comparison with previous studies in other ethnic groups. A total of 27 young male Japanese students performed the BST while measures of muscle fatigue were collected. The mean BST time (152.7 (32.5) s) was greater than the median of the reported mean times in other ethnic groups over the previous decade (128.6 s). Objective measures indicated that the Japanese subjects’ lumbar muscles were as fatigued as those of previous studies, while subjective measures appear to indicate that subjects under-reported exertion. The better performance of the Japanese subjects in the BST may reflect physical, psychosocial and lifestyle differences related to ethnicity.